A laboratory assessment of the potential effect of Cry1Ab/Cry2Aj-containing Bt maize pollen on Folsomia candida by toxicological and biochemical analyses. (March 2017) - Zhang, Bing; Yang, Yan; Zhou, Xiang; Shen, Ping; Peng, Yufa; Li, Yunhe
Abstract: The common soil arthropod Folsomia candida can survive well when fed only maize pollen and thus may be exposed to insecticidal proteins by ingesting insect-resistant genetically engineered maize pollen containing Bacillus thuringiensis ( Bt ) proteins when being released into the soil. Laboratory experiments were conducted to assess the potential effects of Cry1Ab/Cry2Aj-producing transgenic Bt maize (Shuangkang 12–5) pollen on F . candida fitness. Survival, development, and the reproduction were not significantly reduced when F. candida fed on Bt maize pollen rather than on non- Bt maize pollen, but these parameters were significantly reduced when F. candida fed on non- Bt maize pollen containing the protease inhibitor E-64 at 75 μg/g pollen. The intrinsic rate of increase ( r m ) was not significantly reduced when F . candida fed on Bt maize pollen but was significantly reduced when F . candida fed on non- Bt maize pollen containing E−64. The activities of antioxidant-related enzymes in F. candida were not significantly affected when F. candida fed on Bt maize pollen but were significantly increased when F. candida fed on non- Bt pollen containing E−64. The results demonstrate that consumption of Bt maize pollen containing Cry1Ab/Cry2Aj has no lethal or sublethal effects on F. candida. Graphical abstract: Highlights: A validated dietary exposure assay for assessing the effect of GE plant pollen on the springtails. Cry1Ab/2Aj-containing maize pollen does not negatively affect on the fitness of F. candida . The antioxidant-related enzyme activities in F. candida were not significantly affected. Planting cry1Ab/2Aj -expressing maize will pose a negligible risk to the springtails.